SURGICAL TREATMENT OF HIATAL HERNIA: indications, techniques, and outcomes - Isomutdinov, A.Z. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Surgical treatment remains the mainstay of management for symptomatic or complicated hiatal hernias. Advances in minimally invasive techniques have improved postoperative recovery and reduced morbidity, but the optimal surgical approach continues to evolve. This review discusses current indications for surgery, procedural selection based on hernia type, and technical considerations in laparoscopic repair, including cruroplasty, fundoplication, and mesh reinforcement. Attention is given to preoperative evaluation, recurrence prevention, and the management of complex or recurrent hernias. Outcomes, complications, and quality-of-life data are critically reviewed, with emphasis on tailoring surgical strategies to patient-specific anatomy and risk profile.